The Academic Buoyancy Scale: Measurement Invariance across Culture and Gender in Egyptian and Omani Undergraduates - Mustafa Ali Khalaf (RU Publications, 2021)
The academic buoyancy scale (ABS) is one of the most widely used instruments for measuring academic buoyancy. To obtain meaningful and valid comparisons across groups using ABS, however, measurement invariance should be ascertained a priori. To that end, we examined its measurement invariance, validity evidence based on relations to other variables, and score reliability using categorical omega across culture and gender among Egyptian and Omani undergraduates. Participants were 345 college students: Egyptian sample (N=191) and Omani sample (N=154). To assess measurement invariance across culture and gender, multiple–group confirmatory factor analysis was performed with four successive invariance models: (a) configural, (b) metric, (c) scalar, and (d) residual. Results revealed that the unidimensional baseline model had adequate fit to the data in the full sample. Moreover, measurement invariance was found to hold across culture but not across gender and consequently the ABS could be used to yield valid cross-cultural comparisons between the Egyptian and Omani students. Conversely, it cannot be used to yield valid inferences related to comparing gender groups within each culture. Validity evidence based on relations to other variables was supported by the significantly moderate correlation between ABS and academic achievement (GPA; r =.435 and r = .457, P < .01) for the Egyptian and Omani samples, respectively. With regard to score reliability, categorical omega coefficients were moderate across both samples. Educational and psychological implications, limitations and suggestions for improving the scale are discussed.